Covid-19 Awareness for Baiturrahmah Padang Bachelor of Dental Medicine Students - Sri pandu utami Pandu; Intan Batura Endo Mahata; Hiranti Syorga Harien (Denta Journal Kedokteran Gigi, 2022)
Background: Coronavirus, or SARS-CoV2, is one of the main pathogens that attack the human respiratory system. The coronavirus disease caused by SARS COV2 represents the causative agent of a potentially fatal disease of global public health concern. West Sumatra is in the top 10 provinces that contributed the most COVID-19 cases in Indonesia. 1st According to the official website of the Health Padang City Service on September 22, 2020, 2385 confirmed COVID-19 people, 1426 people recovered from COVID-19, and 53 people died.  The high incidence of positive cases of Covid-19 in Padang is due to a lack of public knowledge and adherence to government-mandated health practices. Dental care places have a risk of COVID-19 infection due to aerosols generated during procedures, handling of sharp objects, and the proximity of dentists to patients. Dentistry students must have an awareness of deep knowledge, a better understanding, and must be updated with the practice of adapting to identify possible COVID-19 infections. Objective: The aim is to increase awareness about COVID-19 among undergraduate dentistry students at the Baiturrahmah Faculty of Dentistry, Padang. Methods: This type of research is called descriptive research. The target population of this study was undergraduate dentistry students in 2017, 2018, and 2019, with a sample of 175 people. This research was conducted online in the city of Padang using Google Forms Media for distributing questionnaires. When the research was carried out in September 2020. Results:  The results showed that as many as 99.4% of respondents had good knowledge awareness about COVID-19, 0.6% awareness of bad knowledge, 97.7% of respondents got the first information about COVID-19 through the media, 56% of respondents got the latest Covid information via the internet, only 11.4% of respondents are taking Covid-19 courses, and 5.1% are still taking courses until now. The method of data analysis in this study used the SPSS program with univariate and bivariate analysis. The processed data is presented in table form. Conclusion: Students have awareness about COVID-19.